A Review on the Health Benefits of Kalakai (Stenochlaena Palustris) - Pandiangan, Febbyandi Isnanda; Oslo, Edrick Alvaro; Destine, Fiona; Josephine, Josephine; Anwar, Rania Nadira (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2022)
Kalakai (Stenochlaena palustris) is a common plant in Kalimantan and Sumatra which has been consumed locally as a vegetable. Information about the benefits of kalakai as a functional food has spread widely in the community. However, scientific information and research investigating the potency of kalakai are scarce, and the scientific literature is dominated by local Indonesian-language journals. This review aims to explore and compile the potential health benefits of kalakai based on its nutritional and bioactive content. Kalakai is reported to have various health benefits such as high fibre, antianemia, antioxidant, antidiabetic and antimicrobial activity. Referring to the current status of research, the processing of kalakai as a food functional or nutraceutical ingredient for antioxidative function and controlling blood sugar are the most potential. However, clinical and safety trials still need to be carried out as part of the preparation for the use of kalakai as a functional and nutraceutical food ingredient in the near future.